The Porcine 2A10 Antigen Is Homologous to Human CD163 and Related to Macrophage Differentiation - Carmen Sánchez‐Torres; Nieves Doménech; Jesús Vázquez; Fernando Sánchez‐Alonso; Ángel Ezquerra; Javier Domı́nguez (1999)
Abstract The mAb 2A10 recognizes a 120-kDa protein with sequence homology to the human CD163 and whose expression is restricted to the cells of the porcine monocyte/macrophage lineage. While most of tissue macrophages express high levels of 2A10 Ag, bone marrow cells and a subset of blood monocytes are negative for this marker. The percentage of 2A10+ blood monocytes ranges between 5–50% depending on the donor. The phenotypic analysis indicates that these cells are more similar to mature macrophages than 2A10− monocytes. 2A10+ monocytes express higher levels of swine histocompatibility leukocyte Ag II, CD16, and the adhesion molecules very late Ag-4 (CD49d) and LFA-1 (CD11a) than 2A10− monocytes, while CD14 and SWC1 expression is lower. Both monocyte subsets also differ in their functional capabilities. 2A10+ monocytes induce a greater allogeneic response on T lymphocytes than 2A10− cells. LPS-stimulated 2A10+ and 2A10− monocytes both produce proinflammatory cytokines (TNF-α and IL-1α), but antiinflammatory IL-10 is only detected on the latter population. When 2A10− monocytes were cultured in medium containing pig serum, they acquired some phenotypic features of 2A10+ cells, expressing the 2A10 Ag. In contrast, when they were cultured in the presence of L929 supernatant as a source of GM-CSF, the 2A10 Ag expression remained low, scarcely increasing over basal levels. 2A10+ cells cultured with pig serum developed features that resemble monocyte-derived dendritic cells. These results indicate that 2A10+ monocytes could constitute a cell population in a more advanced maturation stage than 2A10− circulating monocytes.